2015
DOI: 10.1186/s12889-015-2448-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise at the workplace prevents deterioration of work ability among healthcare workers: cluster randomized controlled trial

Abstract: BackgroundImbalance between individual resources and work demands can lead to musculoskeletal disorders and reduced work ability. The purpose of this study was to investigate the effect of workplace- versus home-based physical exercise on work ability among healthcare workers.MethodsTwo hundred female healthcare workers (Age: 42.0, BMI: 24.1, work ability index [WAI]: 43.1) from 18 departments at three Danish hospitals participated (Copenhagen, Denmark, Aug 2013—Jan 2014). Participants were randomly allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 39 publications
1
76
0
6
Order By: Relevance
“…Even though many previous studies have reported no or only minor effects of interventions aiming to improve work ability, several recent studies shows that physical exercise at the workplace have the ability to influence work ability (48,49). For instance, ten weeks of strength training improved work ability in relation to physical and mental demands of the job -ie, the same questions as used in the present study -in both slaughterhouse workers with chronic pain and work disability and in healthcare workers (48,49).…”
Section: Sundsturp Et Almentioning
confidence: 61%
See 1 more Smart Citation
“…Even though many previous studies have reported no or only minor effects of interventions aiming to improve work ability, several recent studies shows that physical exercise at the workplace have the ability to influence work ability (48,49). For instance, ten weeks of strength training improved work ability in relation to physical and mental demands of the job -ie, the same questions as used in the present study -in both slaughterhouse workers with chronic pain and work disability and in healthcare workers (48,49).…”
Section: Sundsturp Et Almentioning
confidence: 61%
“…For instance, ten weeks of strength training improved work ability in relation to physical and mental demands of the job -ie, the same questions as used in the present study -in both slaughterhouse workers with chronic pain and work disability and in healthcare workers (48,49). Future research should investigate the effect of interventions aimed at increasing physical and mental capacity (eg, by physical activity and cognitive training), and reducing the physical and mental demands of the job (eg, by adjusting the work demands to the capacity of the workers), in workers with multiple chronic diseases and poor work ability.…”
Section: Sundsturp Et Almentioning
confidence: 83%
“…El desarrollo del estudio tuvo una duración de diez semanas, tiempo recomendado para garantizar la mayor permanencia de los participantes (24) . Se realizó una medición de la frecuencia e intensidad de las MME, una semana antes y una semana después de la intervención.…”
Section: Medicionesunclassified
“…Social aspects also represent a solution to the main causes of employee malaise: Several authors have underlined the importance of creating work environments that encourage employees to openly express their emotions to colleagues and managers and of offering training sessions on emotionally demanding work to make employees and managers more conscious about managing emotions (Coates & Howe, 2015); again, Jakobsen et al (2015) found that social relationships and psychological well-being benefit from organized physical exercises at the workplace, since such exercises represent a social experience shared by employees. A positive work environment can help to improve outcomes by creating a positive perception of how processes are made, reducing work stress, and encouraging innovations as a response to environmental and organizational change (De Simone, 2014b).…”
Section: Interpreting the Findingsmentioning
confidence: 99%
“…Sleep disorders comprise the factor that is specifically highlighted with respect to healthcare workers (Poissonnet & Véron, 2000;Rose & Glass, 2009), especially considering the effects of night shift-work and difficult work schedules. Some authors underlined the role of leisure activities and other off-job experiences in buffering the negative effects of the reported factors (Tuisku et al, 2016), since an improved general quality of life may positively affect employee well-being (Preposi Cruz, 2016 d 'Ettorre & Greco, 2016;Einarsen & Matthiesen, 1998;Estrynbehar et al, 1990;Galletta et al, 2016;Jakobsen et al, 2015;Markwell & Wainer, 2009;McVicar, 2003;Niedl, 1996;Nixon et al, 2015;Park et al, 2004;Salmond & Ropis, 2005;Sun et al, 2016;Suresh et al, 2013;A. Yildirim & D. Yildirim, 2007) highlighted the relevance of mobbing, conflicts, lack of rewards and recognition by superiors, work demands, work duration, difficulty in balancing work and family commitments, and work context factors.…”
Section: Interpreting the Findingsmentioning
confidence: 99%